Analisis Kemampuan Penalaran Masalah Matematis Siswa Kelas V SD di Desa Sekuro - Lovika Ardana Riswari; Aini Noor Khofifah; Lailatul Fauziah (Jurnal Lensa Pendas, 2024)
This study aims to analyze the reasoning ability of mathematical problems of grade V elementary school students in Sekuro Village in solving problems on building space material. The ability of mathematical reasoning is one of the basic abilities that students need to have in the process of solving mathematical problems both in learning and in daily activities. The method in this study uses a qualitative descriptive method that aims to describe the reasoning ability of mathematical problems of grade V elementary school students. This research was conducted in grade V elementary school in Sekuro Village. The population in this study is grade V elementary school students in Sekuro Village totaling 5 people. Data collection is carried out by giving questions on the material to build space to students. The data analysis technique uses data reduction, data presentation and conclusions. Based on these results, it is concluded that the reasoning ability of grade V elementary school in Sekuro Village has a fairly good reasoning ability, because the average student already understands the problem and can solve the problem mathematically. Of the 5 students, there is 1 student who has not been able to solve the description questions on the building room material properly, so these students need help from researchers in solving the problem.